Sejarah Multikultural Terhadap Perkembangan Pendidikan Islam - Laia, Muhammad Ridho; Albina, Meyniar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to analyze the history of the multicultural perspective of Islamic education and its relevance in the current educational era. This research uses the literature study method. The results of this research show that: the multicultural history of Islamic education perspective can develop the potential of students and foster mutual respect for ethnic, cultural and religious diversity. The challenge faced is that many people still vilify people of different sects (religions), ethnicities and cultures. As with issues regarding religion. We often hear non-Muslims taking issue with the sound of the call to prayer. They think the sound of the call to prayer disturbs them. This includes the challenge for educators to provide multicultural education to students who have traits that are not tolerant or respectful.